Problems of Food Security in the Regions of the Far North of Russia - Poleshkina, Irina Olegovna (Economy of Regions, 2018)
The article analyzes the issues of food provision of the northern regions of Russia. The development of transport infrastructure is insufficient for the year-round delivery of perishable goods. A lack of research in this field is due to the fact that the transport system in these territories is mainly focused on the delivery of raw materials. The food security was estimated by food supply balances and population surveys. In this study, I use a conceptual model of food security. The food supply security was assessed using two groups of criteria: the availability of food supplies and access to them. The studies have shown that in the regions of the Far North of Russia, the supply of perishable food is insufficient, its assortment is limited, the quality is low at above-market prices. The development of the transport infrastructure is a leading factor that determines the food security in the northern regions. I propose to estimate the efficiency of transport delivery schemes considering the losses from their failures. The calculation of losses can prove that the used delivery schemes are not the most effective ones, and there is a need to develop other schemes of transportation. The comparative analysis of the used transport delivery takes into account the delivery time, the cost of transportation and the risks supply disruptions. This analysis has shown, that in the Far North, the delivery by rail to the Siberian rivers beds with subsequent transportation by river transport is the most demanded way of food supply. This delivery method incurs the minimum transportation costs. However, it is the longest route, and has the highest risk of supply disruptions. The second largest delivery scheme by the volume of food supplies is the Northern Sea Route. It incurs higher transport costs, shorter delivery time and lower risks. The third scheme of delivery is by air transport. It is the most under-utilized way of three routes with the minimum losses from disruptions and the maximum cost. The results of this study can be used to redesign delivery schemes and to identify priority areas for the development of transport infrastructure.